Studi Implementasi Program CSR (Corporate Social Responsibility) Berkelanjutan di Perusahaan Perkebunan Kelapa Sawit - Aang Kuvaini; Jojon Soesatrijo; Adi Prayoga (Politeknik Kelapa Sawit Citra Widya Edukasi, 2021)
CSR (Corporate Social Responsibility) is a concept or action taken by the company as a sense of corporate responsibility towards the social and environmental surroundings of the company. PT Manakarra Unggul Lestari is an oil palm company that has a responsibility to improve the welfare of the community around the plantation in various aspects. This study aims to determine the implementation of CSR programs in oil palm plantation companies and analyze priority CSR programs for communities around oil palm plantations. The method used in this research is a direct survey to the field and structured interviews with key persons. The field survey was conducted to see the condition of the community and the results of the implementation of the CSR program. Structured interviews were conducted with key persons, namely parties in the community who are considered to have knowledge and know in detail about the implementation of CSR programs. The results show that the implementation of PT Manakarra Unggul Lestari's CSR program has been well implemented in the fields of education, and infrastructure, while the health and socio-economic sectors are still considered lacking. There are several CSR programs that are not evenly distributed to all areas of the community, so further socialization is needed.